METODE LIMA LANGKAH ARANSEMEN MUSIK - Singgih Sanjaya, R.M. (Institut Seni Indonesia Yogyakarta, 2013)
This study discusses a music arrangement methodological approach that is based on research and author’s ongoing experience run for more then twnry five years. The study is aimed at contributing a methodic guidance for those who concern with music arrangement. The research output of this study is a formulation of the five steps in music arrangement that encompass: arrangement concept, initial arrangement, creating new idea, further arrangement, and evaluation as well as revision.The author suggests that piano is the best instrument for arrangement and the arranger should actively hear the arrangements of various musical genres.Keywords: music arrangement, five steps, methodic guidance